Organic Optoelectronics: Photoelectronic Conversion Materials, Physics and Devices (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This is a collection of research articles reporting the most recent progress in organic optoelectronic materials and devices. The involved research work covers materials of organic and hybrid semiconductors, designs in micro and nano scales, structures for microcavity and random lasing, and devices for light emission or detection. Although these research results deal with only a narrow band of the broad topic of organic optoelectronics, they are believed to make excellent contributions to the new development of related fields. Appreciations should be delivered to all of the authors, whose support enabled the successful completion of this Special Issue.